2012
DOI: 10.2478/cttr-2013-0917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sugar Content on Acetaldehyde Yield in Cigarette Smoke

Abstract: The relationship between cigarette blend sugar and acetaldehyde formed in its smoke is a matter of current regulatory interest. This paper provides a re-analysis of data from 83 European commercial cigarettes studied in the 1970s and more modern data on sugar levels and acetaldehyde yields from a series of 97 European commercial cigarettes containing both inherent sugar and in other cases inherent and added sugar. It also provides data from 65 experimental cigarette products made from single curing grades of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…The results of this study were confirmed by laboratories of the cigarette industry (177,178). In a recent study, CAHOURS et al (179,180) did not see a correlation between the sugar content of cigarette tobacco and the acetaldehyde level in mainstream smoke. This had also been pointed out by BAKER in 2007 (181).…”
Section: Tobacco Additives That Are Alleged To Increase Nicotine Addisupporting
confidence: 77%
See 3 more Smart Citations
“…The results of this study were confirmed by laboratories of the cigarette industry (177,178). In a recent study, CAHOURS et al (179,180) did not see a correlation between the sugar content of cigarette tobacco and the acetaldehyde level in mainstream smoke. This had also been pointed out by BAKER in 2007 (181).…”
Section: Tobacco Additives That Are Alleged To Increase Nicotine Addisupporting
confidence: 77%
“…They had concluded that sugars in tobacco blends accounted for an additional 11% variance in aldehydes. However, CA-HOURS et al (180) argued that the multivariate analysis approach used by O'CONNOR and HURLEY was incomplete and had generated misleading conclusions. Furthermore, CAHOURS et al (180) recognized no difference between the mainstream smoke acetaldehyde yields of cigarettes with American blends, dark air cured or flue cured tobaccos, irrespective of their sugar content when NFDPM yields were taken into account.…”
Section: Sugarsmentioning
confidence: 99%
See 2 more Smart Citations
“… 8–10 Drying (curing) of the leaf can affect these contents; while air-cured tobacco contains virtually no sugars, flue-cured tobacco may contain concentrations up to 25% of its weight. 11 , 12 Different types of sugars and sugar-containing ingredients, such as honey and fruit syrups, are added during manufacturing as binder, casing ingredient, flavor, formulation aid, or humectant. 10 , 11 , 13 Combustion and pyrolysis processes of sugars, such as caramelization, produce many different chemical compounds, including aldehydes, furan derivatives, VOCs, organic acids, acrylamide, and PAHs.…”
Section: Introductionmentioning
confidence: 99%